Ključni poudarki procesa urejanja prostora - Mlakar, Aleš (Podjetje in delo, 2016)
Profession with great reluctance, but also the expectations and willingness to cooperate actively monitors the formation of the new Spatial Management Act. The basic criticism of hitherto amends of spatial planning legislation is that has not been sufficiently taken into account theoretical/professional foundations of spatial planning. The purpose of this paper is to refute some of the myths associated with preparing of spatial legislation and to draw attention to key positions, the purpose and content of the process of spatial planning, which should be considered/enabled within the new spatial planning legislation.
Keywords: pravna ureditev; prostorsko planiranje; prostorsko urejanje